PENGARUH KESADARAN EMOSIONAL, RASA PERCAYA DIRI, KONTROL EMOSIONAL TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS (SMA) - Mon, Muhammad Donal (Journal of Global Business and Management Review, 2019)
The performance of high school teachers (SMA) is very important in education, several factors that influence emotional intelligence from the teacher itself. On this occasion the independent variable was emotional self-awareness, self-confidence, emotional self control, while the dependent variable was teacher performance. Research data retrieve using a questionnaire, to measure how much influence emotional intelligence has on teacher performance. Data is processed using the SPPS program. The results of the analysis show that two variables of emotional intelligence have a positive and significant effect on teacher performance while self-confidence has a positive and not significant effect on teacher performance. Furthermore, the adjusted R square is obtained at 65.0%, influenced by these three factors, 35% is the contribution of other variables not included in this study.